1997
DOI: 10.1093/sleep/20.8.654
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Arousal From Sleep: Mechanisms and Significance

Abstract: The mechanisms by which respiratory stimuli induce arousal from sleep and the clinical significance of these arousals have been explored by numerous studies in the last two decades. Evidence to date suggests that the arousal stimulus in nonrapid eye movement sleep (NREM) is related to the level of inspiratory effort rather than the individual stimuli that contribute to ventilatory drive. A component of the arousal stimulus proportional to the level of inspiratory effort may originate in mechanoreceptors either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
174
0
16

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(197 citation statements)
references
References 0 publications
7
174
0
16
Order By: Relevance
“…As a surrogate for respiratory arousability, we analyzed average apnea and hypopnea event duration length, with shorter duration events indicating greater arousability (49). This phenotype was only moderately correlated with AHI (r = 0.220).…”
mentioning
confidence: 99%
“…As a surrogate for respiratory arousability, we analyzed average apnea and hypopnea event duration length, with shorter duration events indicating greater arousability (49). This phenotype was only moderately correlated with AHI (r = 0.220).…”
mentioning
confidence: 99%
“…SDB is a significant health problem in adults (6), greatly impacting quality of life (7,8). CSA, characterized by an absence of respiratory effort, is less common in young adults but becomes increasingly prevalent with age (11,12), even in elderly individuals who are relatively ''healthy'' (16). The etiology of CSA is presently unknown; however, we show here and have shown previously (5) that disruption of preBö tC function may be an underlying or contributing cause.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment resulted in a significant reduction of nocturnal periodic limb movements and improvement on the MWT. SAS, RLS and PLMD are prevalent in patients with advanced kidney disease and could explain EDS, but some studies suggested that other factors related to renal disease or its treatment may contribute to EDS (52,53).…”
Section: Excessive Day Time Sleepinessmentioning
confidence: 99%